Uganda’s 2006 Presidential and Parliamentary Elections - Gloppen, S.; Atoo, C.; Kasimbazi, E.; Kibandama, A.; Kiiza, J.; Makara, S.; Okiror, G.; Rakner, L.; Rwengabo, S.; Svåsand, L.; Tabaro, R.; Tostensen, A. (Chr. Michelsen Institute, 2006)
On Thursday 23 February 2006 Ugandan voters decided who will govern for the next five years.1 These were the first multi-party elections in the country since 1980 and marked the end of 20 years of “no-party democracy”.2 It was also the first tripartite elections, with voters electing the President and parliamentary representatives (including special seats for women) on the same day. An important day indeed,3 but elections are more than the casting and counting of votes. Much is decided in the weeks and months prior to election day, and events in the aftermath of the polling may alter the outcome. To judge an election on the basis of a narrow focus on the polling and tallying of results, and perhaps the last part of the campaign, often yields a very different verdict than if the basis for analysis is the broader process, where the parameters and structures are set that underpin and restrain the electoral process. This report analyses the 2006 presidential and parliamentary election in terms of the broader process starting with the processes of setting the rule for political contestation, through the registration of voters and parties, the nomination of parties and candidates, the campaign, the voting, counting and tallying and finally, the handling of election complaints. The report shows how problems and irregularities at various stages of the election cycle tilted the playing field and compromised the integrity of the 2006 elections. The report comes out of research collaboration between the departments of Political Science and Public Administration, Public and Comparative Law (Makerere University) and the Chr. Michelsen Institute in Bergen, Norway. The project analyses the development of democratic processes in Uganda by focusing on institutions aimed at securing democratic accountability. To ensure that elected political leaders ‘play by the rules’ and act in accordance with their mandate without violating citizens’ rights, is a key challenge for new democracies in sub-Saharan Africa, and elections and succession ‘test’ the strength of political institutions to check against executive dominance. In many cases incumbents find ways to win electoral mandates without opening for genuine political competition, and we ask to what extent the institutions established to guard against executive dominance in Uganda were able to exercise their functions in the context of the 2006 elections.